2017
DOI: 10.3389/feduc.2017.00031
|View full text |Cite
|
Sign up to set email alerts
|

Intercultural Comfort through Social Practices: Exploring Conditions for Cultural Learning

Abstract: High-quality cross-ethnic interactions contribute to college students' development, but knowledge is scant concerning campus settings and conditions that promote these interactions. This study indicates that distinct social practices in particular settings create such conditions. Phenomenological analysis of current and past members of a voluntary community service association (a pseudonym), appropriated to meet their social needs, revealed practices leading students from differing ethnic backgrounds to challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…This study found no significant relationship between the perceived percent of immigrants in schools and levels of intergroup contact, suggesting that intergroup contact is not a passive process: a diverse social environment does not necessarily lead to increased intergroup contact. This finding is supported by existing literature (Bernstein & Salipante, 2017;Janmaat, 2014;Kiehne, 2019;Robinson et al, 2020). While schools meet the requirements for positive, equal intergroup contact, only youth predisposed to, or encouraged to, initiate contact will likely experience positive effects.…”
Section: Understanding Diversity Threat and Immigrationsupporting
confidence: 73%
See 1 more Smart Citation
“…This study found no significant relationship between the perceived percent of immigrants in schools and levels of intergroup contact, suggesting that intergroup contact is not a passive process: a diverse social environment does not necessarily lead to increased intergroup contact. This finding is supported by existing literature (Bernstein & Salipante, 2017;Janmaat, 2014;Kiehne, 2019;Robinson et al, 2020). While schools meet the requirements for positive, equal intergroup contact, only youth predisposed to, or encouraged to, initiate contact will likely experience positive effects.…”
Section: Understanding Diversity Threat and Immigrationsupporting
confidence: 73%
“…The prevalence of discrimination suggests that there is a need for prejudice reduction, for both educational staff and students. Contact-based interventions may be one method for promoting positive intergroup relationships and addressing anti-immigrant and ethnic prejudices, and would require the promotion of positive contact, which does not always occur organically, even in diverse environments (Bernstein & Salipante, 2017;Kiehne, 2019).…”
Section: Intergroup Contactmentioning
confidence: 99%
“…Civil norms of tolerant but superficial interaction on campus can produce discomfort and intercultural apprehension, which in turn can hinder meaningful interaction and learning (Bernstein & Salipante, 2017). Thus, it is possible that Website: www.ijreeonline.com, Email: info@ijreeonline.com Volume 7, Number 2, June 2022 medical students with different levels of ethnocentrism could possibly feel differently about learning English in culturally diverse settings of their classrooms at university.…”
Section: Ethnocentrism and Iranian Medical Studentsmentioning
confidence: 99%